The role of vitamin D in the course of SARS-CoV-2 infection and long COVID in children (literature review) - L.A. Volianska; E.I. Burbela; T.M. Kosovska; V.O. Perestyuk; O.R. Boyarchuk (Zaslavsky O.Yu., 2023)
Long-term observation of the SARS-CoV-2 pandemic in the pediatric population revealed the presence of persistent symptoms in 1 : 4 to 1 : 10 children four or more weeks after the onset of this infection. The question about the role of vitamin D in the course of COVID-19 and the development of long-term health conditions is still debatable. The purpose of this review is to generalize and clarify the effect of vitamin D on the course of COVID-19 and the post-COVID period in children. Electronic search for scientific publications was done in the PubMed, Scopus, ResearchGate, Wiley Online Library and Google Scholar databases from 2019 to February 2023. Analysis of studies on COVID-19, the post-COVID period, and the impact of hypovitaminosis D on their course attests to the ambiguity of published results in the pediatric cohort. A number of researchers have linked vitamin D deficiency to higher mortality, higher hospitalization rates, and longer hospital stays. Hypovitaminosis D impairs the functioning of the immune system in an organism infected with the pandemic coronavirus, which increases the risk of severe course and mortality. But this hypothesis still needs in-depth study to understand the essence of the effect of vitamin D supplementation on the course of the coronavirus infection and long COVID. The hypothesis about the relationship between hypovitaminosis D and immunosuppression during infection with a pandemic coronavirus and its potential role in the formation of long-term health conditions after acute COVID-19 is still under permanent study.